Production Of Surfactin By Using Local Isolates Of Bacillus Subtilis - Amena A. Abdulrazeg (Universiti Sains Islam Malaysia, 2015)
Bacillus subtilis is able to synthesize surfactin with excellent surface-active properties and biological activities. Since local isolates of B. subtilis are abundant and cheap, quantification and identification of surfactin produce by four local isolates of B. subtilis named as 1M, 3M, 7M, and 8M were studied by through shake flasks fermentation and high performance liquid chromatography (HPLC). The experimental work was conducted to develop modified method of HPLC technique for surfactin quantification and identification, as well as to assess the ability of four local isolates to produce surfactin using Cooper’s media in shake flasks fermentation under the condition of 200 rpm for 168 h at 30oC. The produced surfactin were compared with the commercial strain of B. subtilis ATCC 21332. In addition, various concentrations of glucose and manganese were added to the fermentation media to investigate its effects on surfactin production. Increasing the solvent system of acetonitrile-deionised water at 80:20 % (v/v) with 1.5 mL/min flowrate showed significant rapid elution of surfactin isoform which also proved that four local isolates strains have the ability to produce surfactin. The results obtained show that the maximum surfactin production and bacterial growth of both local and commercial strains were at 96 hours and 72 hours of fermentation, respectively. Moreover, B. subtilis 3M showed the highest amount of surfactin production, while B. subtilis 1M strain produced the lowest amount. For B. subtilis 8M, maximum surfactin production was achieved at around 72 h of fermentation, with surfactin yield of 105 ± 12 mg/L and the production of surfactin for B. subtilis 7M in 96 h of fermentation, with surfactin yield of 86 ± 11 mg/L. In addition, Surfactin production of B. subtilis ATCC 21332 strain was significantly higher (P≤ 0.01) in comparison to B. subtilis 1M, whereas no significant difference in surfactin production between B. subtilis ATCC 21332 and B. subtilis 3M. Addition of 0.5mM MnSO4 and 40 mg/L of glucose to the fermentation media managed to increase the yield of surfactin. Finally, fermentation broths recovered and concentrated with Ultrafiltration (UF) device were analyzed with liquid chromatography-mass spectrometer (LC-MS) to determine the molecular mass of surfactin isoforms. The isolates produced series of surfactin isoforms except for B. subtilis 7M. The isolates of B. subtilis 1M, B. subtilis 3M, and B. subtilis 8M produced series of surfactin isoform, which have similarity with surfactin standard isoforms. Furthermore, the local isolates produced new surfactin isoform which has molecular mass of 927 Da. B. subtilis ATCC 21332 as well produced a new surfactin isoform with molecular mass of 1101 Da.